Pemanfaatan Sari Ubi Jalar Ungu (Ipomoea batatas poiret) Sebagai Zat Pewarna Pada Pewarnaan Staphylococcus aureus - yuniarty, Tuty; Misbach, Siti Rachmi (POLTEKKES KEMENKES YOGYAKARTA, 2016)
The sweet potato purple (Ipomoea batatas poiret) is a type of tubers which have a component of starch, consisted of 30-40% amylase and 60-70% amylopectin. In addition, purple sweet potato also contains a lot of antioxidants derived from anthocyanins, which amounted to 110.51 mg/100 g, phenolic compounds contained in anthocyanin pigments which can stain the cell wall is peptidoglycan of gram-positive bacteria, Staphylococcus aureus. The purpose of this research is to determine whether the purple sweet potato essence can be used as an alternative to the staining of Staphylococcus aureus. This study is a Quasi-experimental design, results are compared directly between gram staining results of Staphylococcus aureus on gram staining using purple sweet potato essence as an experimental group and the gram staining using gentian violet as the control group. The results showed the bacteria with coccus form and reddish violet color presented on gram staining of the experimental group and the control group. The conclusion is the essence of purple sweet potato can be used as an alternative to the staining of Staphylococcus aureus.